A vehicle‐mounted high power LPDA design for 8‐22 MHz applications. Issue 4 (8th January 2022) - Zhu, Wenjun; Guo, Lixin; He, Shaolin
Abstract: The design of high‐power vehicle‐mounted log periodic dipole antenna for 8‐22 MHz use was discussed. It is shown that the antenna has a power endurance of 150 kW. With the application of the coefficients variation method, the total size of the proposal was shrunk to 12 × 18 m so that it can be mounted on a vehicle of 10 m long by an elevation tower. The voltage standing wave ratio over the entire frequency band is lower than 2.0 without utilizing any match network.